The Frontier software-defined radio for the solar probe plus mission - Haskins, Christopher B.; Angert, Matthew P.; Sheehi, E. Joseph; Millard, Wesley P.; Adams, Norman; Hennawy, Joseph R. (2016 IEEE Aerospace Conference, 2016)
The latest adaptation of the Frontier Radio, an X/Ka-band deep space implementation, has been transitioned into a finished product for Solar Probe Plus (SPP) and future missions. Leveraging the technology readiness level (TRL) 9 software-defined radio (SDR) platform successfully flown on the Van Allen Probes (VAP) mission, the Frontier Radio now brings a low-power, low-mass, yet highly radiation-tolerant and robust SDR to deep space applications. This implementation brings with it a suite of enhanced capabilities and improvements to the Frontier Radio platform. The core deep space software implementation is designed to match or improve upon the signal acquisition and tracking performance, as well as improve the receive and transmit implementation losses of its predecessors (JHU/APL and industry). The deep space radio operates using less than 6W at 30V in receive mode, and approximately 10W with either the X- or Ka-band exciter enabled and operating in two-way coherent duplex mode. The power consumption in these modes can be further reduced to as low as 3W and 9W respectively, depending on the spacecraft bus and mission requirements. In addition to providing standard deep space navigation features such as two-way Doppler, two-way ranging, and differential one-way ranging (DOR), firmware and software enhancements were made to improve the receiver acquisition and tracking robustness. A software enhancement was also essential in 1) reducing the effects of turnaround noise on the Ka-band link and 2) reducing the impact on downlink frame error rates while operating in a coherent turnaround mode. These improvements enable simultaneous science return and navigation over the Ka-band link with minimal implementation loss. A number of enhancements to the hardware and test platforms have been made to improve manufacturability, reduce manufacturing and test cost and turnaround time, improve portability across multiple frequency bands and applications, and increase processing capacity. The parts selection provides for a total ionizing dose (TID) tolerance of at least 100krads, subject to the parts purchased at time of manufacturing, without spot or bulk shielding. The Frontier Radio provides a robust selection of single event mitigation and fault protection techniques. Future deep space missions such as Europa Clipper plan to utilize the Frontier Radio. A single board version of the Frontier Radio is also under development for CubeSat and other small form factor spacecraft, with a current best estimate (CBE) of 1W receive mode and less than 5W duplex mode with a 1W power amplifier; this implementation leverages the same robust parts selection as the parent product, with a streamlined hardware implementation that leverages advancements in high speed signal conversion and processing. This paper describes the current capabilities of the Frontier Radio for deep space and provides a short discussion of future efforts related to the platform.